Correction to: Equivalence Testing of Complex Particle Size Distribution Profiles Based on Earth Mover’s Distance - Meng Hu; Xiaohui Jiang; Mohammad Absar; Stephanie Choi; Darby Kozak; Meiyu Shen; Yu-Ting Weng; Liang Zhao; Robert Lionberger (The AAPS Journal, 2020)

Development of an Aerosol Dose Collection Apparatus for In Vitro Dissolution Measurements of Orally Inhaled Drug Products - Robert Price; Jagdeep Shur; William Ganley; Gonçalo Farias; Nikoletta Fotaki; Denise S. Conti; Renishkumar Delvadia; Mohammad Absar; Bhawana Saluja; Sau Lee (The AAPS Journal, 2020)
The aim of the study was to develop a robust and standardized in vitro dissolution methodology for orally inhaled drug products (OIDPs). An aerosol dose collection (ADC) system was designed to uniformly deposit the whole impactor stage mass (ISM) over a large filter area for dissolution testing. All dissolution tests were performed under sink conditions in a sodium phosphate buffered saline solution containing 0.2% w /w sodium dodecyl sulphate. An adapted USP Apparatus V, Paddle over Disk (POD), was used throughout the study. The dissolution characteristics of the ISM dose of a commercial metered-dose inhaler (MDI) and a range of dry powder inhaler (DPI) formulations containing inhaled corticosteroids were tested. The uniform distribution of the validated ISM dose considerably reduced drug loading effects on the dissolution profiles for both MDI and DPI formulations. The improvement in the robustness and discriminatory capability of the technique enabled characterization of dissolution rate differences between inhaler platforms and between different DPI product strengths containing fluticasone propionate. A good correlation between in vivo mean absorption time and in vitro dissolution half-life was found for a range of the inhaled corticosteroids. The ADC system and the reproducible in vitro POD dissolution measurements provided a quantitative-based approach for measuring the relationship between the influence of device and the dispersion characteristics on the aerosol dissolution of low solubility compounds. The in vitro dissolution method could potentially be applied as a dissolution methodology for compendial, quality control release testing, and during development of both branded orally inhaled drug products and their generic counterparts.

Scientific Considerations for the Review and Approval of First Generic Mometasone Furoate Nasal Suspension Spray in the United States from the Bioequivalence Perspective - Qing Liu; Mohammad Absar; Bhawana Saluja; Changning Guo; Badrul Chowdhury; Robert Lionberger; Dale P. Conner; Bing V. Li (The AAPS Journal, 2019)

Equivalence Testing of Complex Particle Size Distribution Profiles Based on Earth Mover’s Distance - Meng Hu; Xiaohui Jiang; Mohammad Absar; Stephanie Choi; Darby Kozak; Meiyu Shen; Yu-Ting Weng; Liang Zhao; Robert Lionberger (The AAPS Journal, 2018)

Predicting Pulmonary Pharmacokinetics from In Vitro Properties of Dry Powder Inhalers - Sharvari Bhagwat; Uta Schilling; Mong-Jen Chen; Xiangyin Wei; Renishkumar Delvadia; Mohammad Absar; Bhawana Saluja; Günther Hochhaus (Pharmaceutical Research, 2017)

Effect of Plasticizer on Release Kinetics of Diclofenac Sodium Pellets Coated with Eudragit RS 30 D - Golam Kibria; Monzurul Amin Roni; Mohammad Shahriarul Absar; Reza-ul Jalil (AAPS PharmSciTech, 2008)